S. R. Schram, ed., The Scope of State Power in China, Londres, School of Oriental and African Studies, University of London, The Chinese University Press, The Chinese University of Hong Kong, 1985, 381 pp. - Connelly, Marisela (Estudios de Asia y África, 1988)
-